Detection of salmonella enterica subsp. enterica serovar Typhi from cholecystectomy samples by conventional, serological and molecular methods in Hospital USM - Ghazali, Asmak (2020)
Salmonella enterica subsp. enterica serovar Typhi (S. Typhi) is an agent of typhoid in human. Typhoid has been reported causing 11-20 million people illnesses and estimated 128 000 to 161 000 deaths every year. The bacteria were spread by fecal-oral route through infected food or water. The most common sites of infection are the gallbladder, liver, ileum, spleen and bone marrow. At the moment, removal of the gallbladder through cholecystectomy procedure remains the effective option for typhoid carriers with gallstones. In this study, eighty (80) patients that enrolled for cholecystectomy and having hepatobiliary disease were chosen as sample. A convenience study has been performed to isolate S. Typhi by using four culture techniques; which are direct incubation (technique 1), upper layer collection (technique 2), vortex (technique 3) and supernatant and pellet separation (technique 4), then proceed to conventional polymerase chain reaction (PCR) test and serology test using Typhidot-C. Out of 80 samples, eight samples (Gb9, Gb10, Gb11, Gb15, Gb43, Gb50, Gb64 and Gb74) showed the presence of suspected colonies of Salmonella species on the Hektoen Enteric (HE) agar and Xylose Lysine Deoxycholate (XLD) agar by using supernatant and pellet separation technique. All eight sample of suspected colonies were tested with biochemical test which included triple sugar iron (TSI) test, urease test, citrate test, indole test and methyl red (MR) test. The result showed that all suspected colonies were negative for detection of Salmonella species. Electronic RapID Compendium (ERICTM) test was done and Citrobacter freundii was detected with probability of 99 per cent. From the eight samples mentioned, six samples were shown negative detection of Salmonella species by PCR, meanwhile, two samples were positive by PCR but both samples were negative for Salmonella by biochemical test. Serology test by using Typhidot-C were done and the result showed all 37 blood samples were negative for S. Typhi carrier. As a conclusion, this study not able to isolate and correlate the presence of the S. Typhi in HUSM patients with hepatobiliary diseases in comparison to other typhoid endemic countries. As for recommendation, there is a need to refine the inclusion criteria such as includes the patients that have typhoid history, increase the sample size and collaborate with many hospitals in collecting the samples.